Outcomes of hyperglycaemia in pregnancy in Africa: Systematic review and meta-analysis - Ezekiel Musa; Tawanda Chivese; Mahmoud Werfalli; Larske M. Soepnel; Veronique Nicolaou; Mushi Matjila; Shane A. Norris; Naomi S. Levitt (PLoS ONE, 2026)
Objective The global prevalence of type 2 diabetes mellitus has significantly risen in recent decades, leading to a corresponding increase in the incidence of diabetes-complicated pregnancies. Hyperglycaemia in pregnancy (HIP), the most common metabolic complication encountered during pregnancy, is associated with a range of adverse maternal and foetal outcomes. This systematic review comprehensively examined the maternal, foetal, neonatal, childhood, and long-term maternal outcomes of HIP in Africa. Methods A systematic review of all studies investigating HIP outcomes in Africa from January 1998 to February 2025 was undertaken. We searched PubMed-MEDLINE, Cochrane Library, Scopus, CINAHL (EBSCOhost), Embase and Web of Science databases for eligible studies. Studies were included if they were observational studies describing outcomes of HIP in Africa. For each outcome, study results were synthesised using an inverse variance heterogeneity meta-analysis with the Freeman-Tukey transformation. Heterogeneity was assessed using the I 2 statistic, and publication bias was assessed using Doi plots. Results Thirty studies were included in the review, comprising 9742 participants. These studies were conducted across the following African countries: South Africa (n = 11), Ethiopia (n = 4), Nigeria (n = 3), Sudan (n = 3), Uganda (n = 2), and one each from Ghana, Algeria, Morocco, Democratic Republic of Congo, Zimbabwe, Togo, and Egypt. The most common adverse pregnancy outcomes for gestational diabetes mellitus (GDM) were caesarean section (CS) (overall prevalence 46.0%, 95% CI 35.7–56.4, I 2 = 95.6%), preterm delivery (overall prevalence 25.2% (95% CI 12.7–40.2, I 2 = 96.7%) and neonatal intensive care unit (NICU) admission (overall prevalence 25.9% (95% CI 13.7–40.2, I 2 = 85.7%). The most common adverse pregnancy outcomes for women with preexisting type 1 diabetes (T1DM) were CS (overall prevalence 57.5%, 95% CI 44.9–69.7, I 2 = 81.2%), preterm delivery (overall prevalence 50.7%, 95% CI 16.3–84.8, I 2 = 92.6%), and neonatal hypoglycaemia (overall prevalence 20.2%, 95% CI 0.0–61.4, I 2 = 94.6%). CS (overall prevalence 60.6%, 95% CI 45.5–74.8, I 2 = 93.6%) and preterm delivery (overall prevalence 35.2%, 95% CI 29.5–41.1, I 2 = 49.3%) were the most prevalent adverse pregnancy outcomes for women with preexisting type 2 diabetes (T2DM). Postpartum T2DM was the most common long-term adverse outcome of women who had GDM or hyperglycaemia first detected in pregnancy (HFDP). There was significant heterogeneity across most outcomes. Conclusions The prevalence of adverse outcomes of HIP in Africa is high, in particular CS, preterm delivery and neonatal hypoglycaemia, with higher frequencies in pregestational T1DM and T2DM compared to GDM. Additionally, T2DM prevalence in women post-GDM is about 50%. The outcome data predominantly come from a few studies, indicating the necessity for more high-quality research to improve HIP-related maternal and child health in Africa. The high heterogeneity across most outcomes suggests that their prevalence varies across populations and underscores the need for more high-quality data. PROSPERO Registration Number: CRD42020184573.